Phenotypic stability and flowering tolerance in intermediate photoperiod onion cultivars in the Bolivian Altiplano - Gonzalo, Quispe Choque; Irene, Gutierrez Limachi; Ariel, Santivanez Aguilar [UNESP]; Nancy, Huanca Alanoca (Soc Investigacon Selva Andina, 2024)
Onion in Bolivia plays an important role in the economy and food security; its domestic production contributes to reduce dependence on imports. The objective of this study was to identify stable onion genotypes with tolerance to premature flowering, adapted for production in the Altiplano. One promising line and three intermediate photoperiod cultivars (bulb forming when day length exceeds 13-14 h) were evaluated for yield stability using a randomized complete block design. The trials were carried out in 5 locations in producing areas of this crop, located in the departments of Oruro, La Paz and Cochabamba. The percentage of flowering plants and onion bulb weight were recorded for each plot after harvest. Analysis of variance of locations and genotypes combined was carried out to determine the most stable cultivars using the univariate and multivariate methods of AMMIbiplot and GGEbiplot. The results indicated that the LP-Altiplano line was the most stable in terms of yield at different locations (b(i) =1.13, S(2)d(i)=26.93, R-2=.56, ri(2)=24.63, Wi=125.74). From the main effects of genotype and genotype-environment interaction biplots, the lines with the best yield were Perilla (35.0 t h-1) and LP-Altiplano (34.8 t h-1), showing very stable yield and developed bulbs of shape and size in more than 90 % of the plants evaluated in the different locations. The cultivars Navide & ntilde;a and Globosa, recorded low productivity with 14.5 and 12.1 t ha-1 respectively and were more susceptible to premature flowering (bolting). This last trait significantly reduces bulb quality and makes them unsuitable for commercial planting.
Keywords: Stability; Susceptibility; genotype